Ultra-high-strength concrete for long-span steel tube arch bridge and preparation method thereof
By using modified low-temperature expandable graphite and modified polystyrene microspheres in steel pipe concrete, the problem of steel pipe concrete being de-emphasized in large-span arch bridges is solved, and its mechanical properties and safety are significantly improved.
Patent Information
- Application Number
- CN202310344558.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-04-03
AI Technical Summary
Steel pipe concrete is prone to hollowing out in large-span arch bridges, affecting its mechanical properties and safety.
Modified low-temperature expandable graphite, by adding low-temperature expandable graphite and modified polystyrene microspheres to the concrete, the pores at the interface are filled with their expansion ability when cement hydrates, and modified polystyrene microspheres. The expansion and rupture of the ball releases calcium ion compensator to further repair the cracks.
It effectively improves the problem of air-removing of steel pipe concrete at the interface, improves its mechanical properties, including compressive strength and crack resistance, and ensures the safety of large-span arch bridges.
Smart Images

Figure BDA0004159123460000121
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of steel tube concrete, and more specifically, it relates to ultra-high strength concrete for long-span steel tube arch bridges and a preparation method thereof. Background Art
[0002] Steel Tube Concrete is a material formed by filling concrete into a steel tube. It is the most important form of steel tube-concrete composite structure. Its composite design principle is: the strength and toughness of concrete can be greatly improved by the tightening effect of the steel tube wall; the concrete filled in the steel tube can improve the stability of the structure and reduce the amount of steel used; the cost performance of the composite material is significantly better than the cost performance of the above two materials alone. Due to its high bearing capacity, good plasticity and toughness, good fire resistance and seismic resistance, excellent durability, convenient construction, and good economic benefits, steel tube concrete has been rapidly promoted and applied in large foundations, high-rise buildings, and large-span arch bridges.
[0003] However, it is well known that the steel tube and core concrete of steel tube concrete are easy to separate at the interface, or the core concrete has voids and is not dense, which is also called concrete debonding or debonding. Concrete debonding exists to varying degrees in steel tube concrete arch bridges. Since the premise for steel tube concrete to exert its superiority is that the steel tube and concrete can work together, the debonding will make the two unable to bear the force together as a whole, which will cause the steel tube to fail to play its hoop effect on the concrete in time under low stress, thereby affecting the mechanical properties of steel tube concrete and even endangering the safety of the arch bridge.
[0004] At present, the solution to this problem includes considering the use of steel with a small linear expansion coefficient or steel fiber core concrete, active mineral powder concrete or micro-expansive concrete, etc., which have a certain effect on preventing the degassing, but these solutions still cannot completely solve the problem of degassing of steel tube concrete. Therefore, there is still a lot of room for improvement in improving the degassing problem of concrete and thus improving the mechanical strength of steel tube concrete. Summary of the invention
[0005] In order to improve the problem of hollowing out of steel tube concrete and further improve the strength of steel tube concrete, the present application provides a long-span steel tube arch bridge ultra-high strength concrete and a preparation method thereof.
[0006] In a first aspect, the present application provides a long-span steel tube arch bridge ultra-high strength concrete, which adopts the following technical scheme: an ultra-high strength concrete for a long-span steel tube arch bridge, comprising the following raw materials in parts by weight: 550-650 parts of cement, 50-120 parts of fly ash, 680-720 parts of machine-made sand, 750-1000 parts of crushed stone, 120-150 parts of water, 4-10 parts of water reducer, 3-4.5 parts of steel fiber, 10-15 parts of expansion agent, and 5-25 parts of modified low-temperature expandable graphite;
[0007] The modified low-temperature expandable graphite comprises low-temperature expandable graphite and modified polystyrene microspheres loaded in the low-temperature expandable graphite. The modified polystyrene microspheres comprise a polystyrene layer and an auxiliary agent coated in the polystyrene layer. The auxiliary agent comprises a micro-nano enhancer.
[0008] The problem of hollowing out of steel tube concrete is often caused by the transportation of concrete raw materials, the use of additives such as water reducers in concrete, and the generation of gases during cement hydration. These gases will gradually rise to the interface between the steel tube and concrete during the cement hardening process, so that there are gaps at the interface, resulting in hollowing out. In addition, after long-term service, concrete, especially early shrinkage and cracking, will also lead to the occurrence of hollowing out. The modified low-temperature expandable graphite added in this application is selected in the preparation of raw materials. Low-temperature expandable graphite is not other expandable graphite because the expansion temperature (150-250°C) of ordinary expandable graphite is high, and the temperature of cement hydration heat is 60-90°C. Therefore, low-temperature expandable graphite is selected. On the one hand, the volume expansion of low-temperature expandable graphite during cement hydration can be achieved to fill and block the pores generated during cement hardening; on the other hand, the cement hydration heat can also be absorbed through the expansion process, reducing the possibility of concrete cracking due to large internal and external temperature differences or reducing the possibility of large cracks. In addition, low-temperature expandable graphite is a type of worm-like substance with a loose porous structure. Its structure is loose, porous and curved, with a large surface area, high surface energy, and strong adsorption capacity. The worm-like graphite can be self-interlocking, thereby increasing its softness, resilience and plasticity. Therefore, low-temperature expandable graphite can load modified polystyrene microspheres well.
[0009] The modified polystyrene microspheres are polystyrene that contains at least a micro-nano enhancer and a calcium ion compensator. The purpose is that: the polystyrene microspheres are organic microspheres with a relatively low density. After the enhancer is added inside, the modified polystyrene microspheres have the advantage of high strength; and the addition of the calcium ion compensator enables the modified polystyrene microspheres to carry and provide calcium ions.
[0010] By adopting the above technical scheme, the density of the modified polystyrene microspheres loaded on the modified low-temperature expandable graphite is relatively small, and the low-temperature expandable graphite itself is a porous hydrophobic structure, so the overall density of the modified low-temperature expandable graphite is relatively small. When the concrete slurry containing the modified low-temperature expandable graphite is injected into the steel pipe, the modified low-temperature expandable graphite gradually tends to float above the slurry. When the cement is gradually hydrated, pores are generated, and the low-temperature expandable graphite gradually absorbs the hydration heat and expands to fill the pores generated at the interface; and the modified polystyrene microspheres loaded in the low-temperature expandable graphite can also gradually absorb the hydration heat and expand, on the one hand, the internal pores of the low-temperature expandable graphite are further fully filled, and on the other hand, due to the volume expansion of the modified polystyrene microspheres, the space of the low-temperature expandable graphite is insufficient, so that part of the modified polystyrene microspheres overflow the low-temperature expandable graphite, and the part of the modified polystyrene microspheres can also effectively fill and block the pores at the interface; at this time, since the polystyrene microspheres contain micro-nano enhancers, the mechanical properties of the repaired pores are also guaranteed. The modified low-temperature expandable graphite of the present application can carry the expansion material and the mechanical property strengthening material to the interface at the same time in a relatively concentrated manner, thereby simultaneously playing the effect of repairing and strengthening the interface, thereby improving the problem of voids at the interface of steel tube concrete and the problem of poor mechanical properties.
[0011] Optionally, the modified low-temperature expandable graphite is obtained by dispersing low-temperature expandable graphite and modified polystyrene microspheres in a weight ratio of 1:(1.2-2.6) in a solvent, adding a silane coupling agent, and dispersing and mixing.
[0012] By adopting the above technical scheme, the excessive amount of modified polystyrene microspheres enables the low-temperature expandable graphite to be loaded with sufficient modified polystyrene microspheres; and the addition of the silane coupling agent can further enhance the load strength; thereby making it difficult for the prepared modified low-temperature expandable graphite to separate from the modified polystyrene microspheres and the low-temperature expandable graphite before cement hydration, thereby ensuring the effectiveness of the modified low-temperature expandable graphite.
[0013] Optionally, the particle size of the modified polystyrene microspheres is 20-500 μm.
[0014] By adopting the above technical solution, the modified polystyrene microspheres with the above particle sizes are selected so that they can be better loaded in the expanded graphite.
[0015] Optionally, taking modified polystyrene microspheres as a reference, the modified polystyrene microspheres include the following raw materials in parts by weight: 3-6 parts of micro-nano enhancer, 76-96 parts of polymerizable monomer, 2.4-5.6 parts of initiator, 1.6-7 parts of dispersant, and 0.8-5 parts of surfactant.
[0016] Compared with conventional polystyrene microspheres, the modified polystyrene microspheres of the present application contain more micro-nano enhancers, and the amount of surfactant added is also more; while the amount of the raw material for forming polystyrene: the amount of polymerized monomers is reduced. The reason for adopting such a scheme is that: first, the reduction in the amount of raw materials for forming polystyrene can make the polystyrene layer of the formed modified polystyrene microspheres thinner or even difficult to completely cover the micro-nano enhancers. Then, when the modified polystyrene microspheres are heated and expanded during cement hydration, the polystyrene layer is more likely to rupture, that is, the substances (micro-nano enhancers, surfactants, etc.) coated in the polystyrene layer are easier to release therefrom. The particle size of the micro-nano enhancer is smaller than that of the modified polystyrene microspheres, so it can fill smaller pores and gaps in the concrete, thereby further compensating for the strength of the concrete. Secondly, the purpose of adding excessive surfactants is: on the one hand, when preparing modified polystyrene microspheres, more surfactants can promote the uniform dispersion of micro-nano reinforcing agents and polymerized monomers, prevent the transitional sedimentation of nano reinforcing agents, and ensure the success rate of preparing modified polystyrene microspheres; on the other hand, the surfactants released in the concrete can also improve the surface tension of bubbles in the environment around the modified expanded graphite, achieve further defoaming in the local environment, and thus improve the degassing problem caused by many bubbles at the concrete-steel pipe interface.
[0017] Optionally, the modified polystyrene microspheres are prepared by a method comprising the following steps:
[0018] S1, mixing the polymerization monomer and the initiator evenly to obtain an initial mixed solution;
[0019] S2, after the dispersant, surfactant, micro-nano enhancer and initial mixed solution are uniformly mixed, the temperature is raised to 90-100° C. for reaction to obtain initial microspheres;
[0020] S3, the initial microspheres are obtained after washing, drying and sieving.
[0021] Optionally, the polymerizable monomers are styrene and divinylbenzene in a weight ratio of 1:(0.08-0.12).
[0022] Optionally, the auxiliary agent further includes a calcium ion compensator; taking the modified polystyrene microspheres as a reference, the raw materials of the modified polystyrene microspheres further include 0.2-2 parts of the calcium ion compensator.
[0023] In the present application, the calcium ion compensator is added in micro-nano particle size. The calcium ion compensator is added to the modified polystyrene microspheres. When the modified polystyrene microspheres are heated and expanded, some of the modified polystyrene microspheres can expand and rupture, and slowly release the calcium ion compensator therein; and the released calcium ions can react with cement or unhydrated cement particles to generate needle-shaped calcium aluminate crystals (AFt, hydrated calcium sulfoaluminate) or lamellar monosulfur hydrated calcium sulfate, hydrated calcium sulfoaluminate (AFm), thereby achieving the plugging and repair of cracks and pores at the interface. By adopting the above technical solution, chemical repair (reaction with calcium ions) and physical repair (thermal expansion of polystyrene microspheres and expanded graphite) can be effectively combined, thereby effectively improving the problem of degassing at the interface.
[0024] Optionally, the auxiliary agent further includes a calcium ion compensator; taking the modified polystyrene microspheres as a reference, when the raw materials of the modified polystyrene microspheres further include 0.2-2 parts of the calcium ion compensator, the modified polystyrene microspheres are prepared by a method comprising the following steps:
[0025] S1, mixing the polymerization monomer and the initiator evenly to obtain an initial mixed solution;
[0026] S2, after the dispersant, surfactant, micro-nano enhancer, calcium ion compensator and initial mixed solution are uniformly mixed, the temperature is raised to 90-100° C. for reaction to obtain initial microspheres;
[0027] S3, the initial microspheres are obtained after washing, drying and sieving.
[0028] Optionally, the micro-nano reinforcing agent is selected from one or both of micro-nano basalt powder and nano silicon dioxide.
[0029] By adopting the above technical solution, both micro-nano basalt powder and nano silicon dioxide have high strength and can significantly improve the mechanical strength of the repaired cracks or pores in the concrete.
[0030] Optionally, the calcium ion compensator is selected from any one or more of calcium formate, calcium hydroxide, calcium nitrite, calcium dodecylbenzene sulfonate and calcium lactate.
[0031] Optionally, the water reducer is a polycarboxylic acid high-efficiency water reducer with a water reduction rate of ≥25%.
[0032] Optionally, the crushed stone is limestone crushed stone, granite crushed stone or basalt crushed stone; further optionally, the crushed stone is 5-25 mm continuously graded, and the content of needle-like particles is 4-8wt%.
[0033] Optionally, the fineness modulus of the machine-made sand is 2.5-3.0, and the mud content of the machine-made sand is 0.05-0.15wt%.
[0034] Optionally, the cement is silicate grade 62.5 cement or silicate grade 62.5R cement.
[0035] Optionally, the expansion agent is a magnesium oxide expansion agent.
[0036] Optionally, the tensile strength of the steel fiber is 1100-1800 MPa.
[0037] In the second aspect, the present application provides a method for preparing ultra-high-strength concrete for a long-span steel tube arch bridge, using the following technical solution:
[0038] A method for preparing the above-mentioned ultra-high strength concrete for the long-span steel tube arch bridge, the preparation method comprising the following steps:
[0039] 1) Mix the machine-made sand and gravel in proportion and stir evenly, then add cement, fly ash and expansion agent and continue to stir evenly;
[0040] 2) Mix the water and the water reducing agent and stir them evenly, add 50-70 wt% of the mixed water and the water reducing agent to the mixture obtained in 1) and stir them evenly, then add the modified low-temperature expandable graphite and the steel fiber, stir them evenly, then add the remaining amount of the mixed water and the water reducing agent and stir them evenly to obtain a mixed concrete mixture;
[0041] 3) pouring the concrete mixture into a mold and curing it to obtain the ultra-high-strength concrete for the long-span steel tube arch bridge.
[0042] In summary, this application has the following beneficial effects:
[0043] 1. The raw materials for preparing concrete in the present application include modified low-temperature expandable graphite prepared by modified polystyrene microspheres coated with micro-nano reinforcing agents, which are filled with low-temperature expandable graphite by polystyrene microspheres. When cement hydration releases heat, firstly, the polystyrene microspheres and the low-temperature expandable graphite absorb heat and expand to fill the pores and cracks in the concrete; secondly, the expansion of the polystyrene microspheres further fills the pores of the low-temperature expandable graphite and enhances its mechanical properties; in addition, some polystyrene microspheres rupture after expansion, releasing the contents to further reinforce the smaller pores of the low-temperature expandable graphite; thereby finally achieving the effect of improving the crack resistance and compressive strength of the concrete; in addition, the raw materials of the modified low-temperature expandable graphite (low-temperature expandable graphite and modified polystyrene microspheres) are all light materials, so they tend to float in cement slurry, so that the materials for reinforcing and filling the pores and cracks arrive at the interface between the concrete and the steel pipe together to improve the problem of degassing of the steel pipe concrete.
[0044] 2. The modified polystyrene microspheres in the present application also contain a calcium ion compensator. Therefore, the mechanical properties of the concrete are significantly improved through direct reinforcement of the micro-nano reinforcing agent combined with the chemical reinforcement produced by the chemical reaction between the calcium ion compensator and the unhydrated cement particles; at the same time, the thermal expansion of the low-temperature expandable graphite, the thermal expansion of the modified polystyrene and the product of the chemical reaction of the calcium ion compensator are combined to fill the cracks in the concrete, thereby significantly improving the crack resistance of the concrete.
[0045] 3. In the preparation of modified polystyrene microspheres, less polymerization monomer is added in the present application to reduce the thickness of the polystyrene layer, thereby making the modified polystyrene microspheres easier to rupture after thermal expansion; and relatively more dispersant and surfactant are added in the preparation of modified polystyrene microspheres. The purpose is, on the one hand, to better disperse the organic phase and the inorganic phase when preparing the modified polystyrene microspheres, and on the other hand, after the modified polystyrene microspheres are ruptured due to thermal expansion, the presence of the surfactant can further achieve defoaming of the local environment, thereby reducing the porosity of the concrete. DETAILED DESCRIPTION
[0046] The present application is further described in detail below in conjunction with embodiments.
[0047] Unless otherwise specified, the raw materials involved in this application are all commercially available. Among them, cement is commercially available silicate 62.5 grade cement or silicate 62.5R grade cement; fly ash is Class F II fly ash; the fineness modulus of the machine-made sand is 2.7, the mud content is 0.1wt%, and the apparent density is 2700kg / m 3 , bulk density 2800kg / m 3 The crushed stone is 5-25mm continuous grading, and the content of needle-like particles is 4-8wt%; the expansion agent is a magnesium oxide expansion agent, CAS: 1309-48-4; the water reducer is a polycarboxylic acid early strength type high-efficiency water reducer, the water reduction rate is ≥25%, and the water bleeding rate is ≤50%; the steel fiber is a cut-type steel fiber with a tensile strength of 1250MPa, purchased from Kunming Baiyi Building Materials Manufacturing Co., Ltd.; the low-temperature expandable graphite is purchased from Lingshou Yaoyue Mineral Products Co., Ltd., with an expansion multiple of 150-300 times; the particle size of micro-nano silica is 50-300nm, and the commercially available micro-nano silica is purchased and sieved to obtain a powder of 50-300nm for use; the particle size of micro-nano basalt powder is 0.5-25μm, and the commercially available micro-nano basalt powder is purchased and sieved to obtain a powder of 0.5-25μm for use.
[0048] Preparation example of modified polystyrene microspheres
[0049] Preparation Example 1
[0050] The raw materials for preparing modified polystyrene microspheres are: 3 kg of micro-nano silicon dioxide, 70.37 kg of styrene, 5.63 kg of divinylbenzene (i.e., 76 kg of polymerization monomer), 2.4 kg of benzoyl peroxide, 1.6 kg of 1 wt% polyvinyl alcohol solution, and 0.8 kg of sodium dodecyl sulfate.
[0051] The preparation method of modified polystyrene microspheres is as follows:
[0052] S1. Ultrasonic disperse the above amounts of styrene, divinylbenzene and benzoyl peroxide for 12 minutes to obtain an initial mixed solution for later use.
[0053] S2. Ultrasonic disperse the above-mentioned amounts of dispersant polyvinyl alcohol solution, surfactant sodium dodecyl sulfate and micro-nano silica for 25 minutes, then add the initial mixed solution obtained in step S1 and stir evenly. After heating to 68°C, the droplets of the initial mixed solution gradually form microspheres, and then heat to 90°C to react for 4.5 hours to obtain initial microspheres.
[0054] S3, washing the initial microspheres with water and then with methanol; then drying; and then sieving to obtain modified polystyrene microspheres with a particle size of 20-500 μm.
[0055] Preparation Example 2
[0056] The raw materials for preparing modified polystyrene microspheres are: 6 kg of micro-nano silicon dioxide, 85.71 kg of styrene, 10.29 kg of divinylbenzene (i.e., 96 kg of polymerization monomer), 5.6 kg of benzoyl peroxide, 7 kg of 1 wt% polyvinyl alcohol solution, and 5 kg of sodium dodecyl sulfate.
[0057] The preparation method of modified polystyrene microspheres is as follows:
[0058] S1. Ultrasonic disperse the above amounts of styrene, divinylbenzene and benzoyl peroxide for 20 minutes to obtain an initial mixed solution for later use.
[0059] S2. Ultrasonic disperse the above-mentioned amounts of dispersant polyvinyl alcohol solution, surfactant sodium dodecyl sulfate and micro-nano silica for 35 minutes, then add the initial mixed solution obtained in step S1 and stir evenly. After heating to 72°C, the droplets of the initial mixed solution gradually form microspheres, and then heat to 100°C for reaction for 5.5 hours to obtain initial microspheres.
[0060] S3, washing the initial microspheres with water and then with methanol; then drying; and then sieving to obtain modified polystyrene microspheres with a particle size of 20-500 μm.
[0061] Preparation Example 3
[0062] The raw materials for preparing modified polystyrene microspheres are: 4.5 kg of micro-nano silicon dioxide, 74.55 kg of styrene, 7.45 kg of divinylbenzene (i.e. 82 kg of polymerization monomer), 3.8 kg of benzoyl peroxide, 5.5 kg of 1 wt% polyvinyl alcohol solution, and 4.5 kg of sodium dodecyl sulfate.
[0063] The preparation method of modified polystyrene microspheres is as follows:
[0064] S1. Ultrasonic disperse the above amounts of styrene, divinylbenzene and benzoyl peroxide for 15 minutes to obtain an initial mixed solution for later use.
[0065] S2. Ultrasonic disperse the above-mentioned amounts of dispersant polyvinyl alcohol solution, surfactant sodium dodecyl sulfate and micro-nano silica for 30 minutes, then add the initial mixed solution obtained in step S1 and stir evenly. After heating to 70°C, the droplets of the initial mixed solution gradually form microspheres, and then heat to 95°C to react for 4.0 hours to obtain initial microspheres.
[0066] S3, washing the initial microspheres with water and then with methanol; then drying; and then sieving to obtain modified polystyrene microspheres with a particle size of 20-500 μm.
[0067] Preparation Example 4
[0068] The difference between this preparation example and preparation example 3 is that when preparing the modified polystyrene microspheres, the raw material micro-nano silicon dioxide is completely replaced with an equal weight of micro-nano basalt powder, and the rest is the same as preparation example 3.
[0069] Preparation Example 5
[0070] The difference between this preparation example and preparation example 3 is that the raw materials for preparing modified polystyrene microspheres also include calcium ion compensator calcium formate powder, that is, the raw materials for preparing modified polystyrene microspheres are: 4.5 kg of micro-nano silica, 1 kg of calcium formate powder, 74.55 kg of styrene, 7.45 kg of divinylbenzene (i.e., 82 kg of polymerization monomer), 3.8 kg of benzoyl peroxide, 5.5 kg of 1 wt% polyvinyl alcohol solution, and 4.5 kg of sodium dodecyl sulfate.
[0071] The preparation method of modified polystyrene microspheres is as follows:
[0072] S1. Prepare the initial mixed solution in the same manner as in Preparation Example 3.
[0073] S2. Ultrasonic dispersion of the above-mentioned amounts of dispersant polyvinyl alcohol solution, surfactant sodium dodecyl sulfate, calcium formate powder and micro-nano silicon dioxide for 30 minutes, and then the subsequent steps are the same as those in Preparation Example 3 to obtain initial microspheres.
[0074] S3. The same method as Preparation Example 3 is used to obtain modified polystyrene microspheres.
[0075] Preparation Example 6
[0076] The difference between this preparation example and preparation example 5 is that the calcium ion compensator for preparing modified polystyrene microspheres is a mixture of calcium formate powder and calcium dodecylbenzene sulfonate powder, that is, the raw materials for preparing modified polystyrene microspheres are specifically: 4.5 kg of micro-nano silica, 0.5 kg of calcium formate powder, 0.5 kg of calcium dodecylbenzene sulfonate powder, 74.55 kg of styrene, 7.45 kg of divinylbenzene (i.e., 82 kg of polymerization monomer), 3.8 kg of benzoyl peroxide, 5.5 kg of 1 wt% polyvinyl alcohol solution, and 4.5 kg of sodium dodecylsulfonate.
[0077] The preparation method of modified polystyrene microspheres is as follows:
[0078] S1. Prepare the initial mixed solution in the same manner as in Preparation Example 5.
[0079] S2. Ultrasonic dispersion of the above-mentioned amounts of dispersant polyvinyl alcohol solution, surfactant sodium dodecyl sulfate, calcium formate powder, calcium dodecylbenzene sulfonate powder and micro-nano silicon dioxide for 30 minutes, and then the subsequent steps are the same as those in Preparation Example 5 to obtain initial microspheres.
[0080] S3. The same method as Preparation Example 5 is used to obtain modified polystyrene microspheres.
[0081] Preparation Example 7
[0082] The difference between this preparation example and preparation example 6 is that the raw materials for preparing modified polystyrene microspheres do not include micro-nano silica, that is, the raw materials for preparing modified polystyrene microspheres are: 0.5 kg of calcium formate powder, 0.5 kg of calcium dodecylbenzenesulfonate powder, 74.55 kg of styrene, 7.45 kg of divinylbenzene (i.e., 82 kg of polymerization monomer), 3.8 kg of benzoyl peroxide, 5.5 kg of 1 wt% polyvinyl alcohol solution, and 4.5 kg of sodium dodecylsulfonate.
[0083] The preparation method of modified polystyrene microspheres is as follows:
[0084] S1. Prepare the initial mixed solution as in Preparation Example 6.
[0085] S2. Ultrasonic disperse the above-mentioned amounts of dispersant polyvinyl alcohol solution, surfactant sodium dodecyl sulfate, calcium dodecylbenzenesulfonate powder and calcium formate powder for 30 minutes, and then perform the same steps as in Preparation Example 6 to obtain initial microspheres.
[0086] S3. The same method as Preparation Example 6 is used to obtain modified polystyrene microspheres.
[0087] Preparation example of modified low temperature expandable graphite
[0088] Preparation Example 1
[0089] Preparation method of modified low-temperature expandable graphite: Disperse low-temperature expandable graphite and modified polystyrene microspheres in a weight ratio of 1:1.2 in water, add silane coupling agent of 0.1wt% of low-temperature expandable graphite, stir and disperse to obtain modified low-temperature expandable graphite. The modified polystyrene microspheres of this preparation example are prepared by modified polystyrene microsphere preparation example 1.
[0090] Preparation Example 2
[0091] Preparation method of modified low-temperature expandable graphite: Disperse low-temperature expandable graphite and modified polystyrene microspheres in a weight ratio of 1:2.6 in water, add silane coupling agent of 0.1wt% of low-temperature expandable graphite, stir and disperse to obtain modified low-temperature expandable graphite. The modified polystyrene microspheres of this preparation example are prepared by modified polystyrene microsphere preparation example 2.
[0092] Preparation Example 3
[0093] Preparation method of modified low-temperature expandable graphite: Disperse low-temperature expandable graphite and modified polystyrene microspheres in a weight ratio of 1:2 in water, add silane coupling agent of 0.1wt% of low-temperature expandable graphite, stir and disperse to obtain modified low-temperature expandable graphite. The modified polystyrene microspheres of this preparation example are prepared by modified polystyrene microsphere preparation example 3.
[0094] Preparation Example 4
[0095] The only difference between this preparation example and preparation example 3 is that the raw material modified polystyrene microspheres for preparing the modified low-temperature expandable graphite are prepared by the modified polystyrene microspheres preparation example 4.
[0096] Preparation Example 5
[0097] The only difference between this preparation example and preparation example 3 is that the raw material modified polystyrene microspheres for preparing the modified low-temperature expandable graphite are prepared from the modified polystyrene microspheres preparation example 5.
[0098] Preparation Example 6
[0099] The only difference between this preparation example and preparation example 3 is that the raw material modified polystyrene microspheres for preparing the modified low-temperature expandable graphite are prepared from the modified polystyrene microspheres preparation example 6.
[0100] Preparation Example 7
[0101] The only difference between this preparation example and preparation example 3 is that the raw material modified polystyrene microspheres for preparing the modified low-temperature expandable graphite are prepared from the modified polystyrene microspheres preparation example 7.
[0102] Preparation Example 8
[0103] The only difference between this Preparation Example and Preparation Example 6 is that the weight ratio of the low-temperature expandable graphite and the modified polystyrene microspheres used to prepare the modified low-temperature expandable graphite is 1:3.
[0104] Preparation Example 9
[0105] The only difference between this Preparation Example and Preparation Example 6 is that the weight ratio of the low-temperature expandable graphite and the modified polystyrene microspheres used to prepare the modified low-temperature expandable graphite is 1:0.8.
[0106] Example
[0107] Example 1
[0108] The raw materials of ultra-high-strength concrete for a long-span steel tube arch bridge are: 550kg of silicate 62.5 grade cement, 50kg of fly ash, 680kg of machine-made sand, 750kg of crushed stone, 120kg of water, 4kg of polycarboxylic acid early-strength high-efficiency water-reducing agent, 3kg of steel fiber, 10kg of magnesium oxide expansion agent, and 5kg of modified low-temperature expandable graphite; the modified low-temperature expandable graphite is prepared by modified low-temperature expandable graphite preparation example 1.
[0109] The preparation method of ultra-high strength concrete for long-span steel tube arch bridge is as follows:
[0110] 1) Mix the machine-made sand and gravel in proportion and stir evenly, then add silicate 62.5 grade cement, fly ash and magnesium oxide expansion agent and continue to stir evenly;
[0111] 2) Mix water and polycarboxylic acid early strength type high efficiency water reducing agent and stir evenly, add 50wt% of the mixed water and water reducing agent to the mixture obtained in 1) and stir evenly, then add all the modified low temperature expandable graphite and steel fiber, stir evenly, then add the remaining amount of the mixed water and polycarboxylic acid early strength type high efficiency water reducing agent and stir evenly, so as to obtain a mixed concrete mixture;
[0112] 3) The concrete mixture obtained in 2) is poured into a mold and cured to obtain ultra-high-strength concrete for a large-span steel tube arch bridge.
[0113] Example 2
[0114] The raw materials of ultra-high-strength concrete for a long-span steel tube arch bridge are: 650 kg of silicate 62.5 grade cement, 120 kg of fly ash, 720 kg of machine-made sand, 1000 kg of crushed stone, 150 kg of water, 10 kg of polycarboxylic acid early-strength high-efficiency water-reducing agent, 4.5 kg of steel fiber, 15 kg of magnesium oxide expansion agent, and 25 kg of modified low-temperature expandable graphite; the modified low-temperature expandable graphite is prepared by modified low-temperature expandable graphite preparation example 2.
[0115] The preparation method of ultra-high strength concrete for long-span steel tube arch bridge is as follows:
[0116] 1) Same as Example 1;
[0117] 2) Mix water and polycarboxylic acid early strength high efficiency water reducing agent and stir evenly, add 70wt% of the mixed water and water reducing agent to the mixture obtained in 1) and stir evenly, and the subsequent steps are the same as in Example 1 to obtain a mixed concrete mixture;
[0118] 3) As in Example 1, ultra-high strength concrete for a long-span steel tube arch bridge is obtained.
[0119] Example 3
[0120] The raw materials of ultra-high-strength concrete for a long-span steel tube arch bridge are: 500 kg of silicate 62.5R grade cement, 80 kg of fly ash, 700 kg of machine-made sand, 900 kg of crushed stone, 130 kg of water, 6.5 kg of polycarboxylic acid early-strength high-efficiency water-reducing agent, 3.5 kg of steel fiber, 12 kg of magnesium oxide expansion agent, and 20 kg of modified low-temperature expandable graphite; the modified low-temperature expandable graphite is prepared by modified low-temperature expandable graphite preparation example 3.
[0121] The preparation method of ultra-high strength concrete for long-span steel tube arch bridge is as follows:
[0122] 1) Same as Example 1;
[0123] 2) Mix water and polycarboxylic acid early strength type high efficiency water reducing agent and stir evenly, add 60wt% of the mixed water and water reducing agent to the mixture obtained in 1) and stir evenly, and the subsequent steps are the same as in Example 1 to obtain a mixed concrete mixture;
[0124] 3) As in Example 1, ultra-high strength concrete for a long-span steel tube arch bridge is obtained.
[0125] Example 4
[0126] The difference between this embodiment and embodiment 3 is that the modified low-temperature expandable graphite for preparing ultra-high-strength concrete for large-span steel tube arch bridge is prepared by modified low-temperature expandable graphite preparation example 4, and the rest is the same as embodiment 3.
[0127] Example 5
[0128] The difference between this embodiment and embodiment 3 is that the modified low-temperature expandable graphite for preparing ultra-high-strength concrete for large-span steel tube arch bridge is prepared by modified low-temperature expandable graphite preparation example 5, and the rest is the same as embodiment 3.
[0129] Embodiment 6 (optimal)
[0130] The difference between this embodiment and embodiment 3 is that the modified low-temperature expandable graphite for preparing ultra-high-strength concrete for large-span steel tube arch bridge is prepared by modified low-temperature expandable graphite preparation example 6, and the rest is the same as embodiment 3.
[0131] Example 7 (Comparative Example)
[0132] The difference between this embodiment and embodiment 3 is that the modified low-temperature expandable graphite for preparing ultra-high-strength concrete for large-span steel tube arch bridge is prepared by modified low-temperature expandable graphite preparation example 8, and the rest is the same as embodiment 3.
[0133] Example 8 (Comparative Example)
[0134] The difference between this embodiment and embodiment 3 is that the modified low-temperature expandable graphite for preparing ultra-high-strength concrete for large-span steel tube arch bridge is prepared by modified low-temperature expandable graphite preparation example 9, and the rest is the same as embodiment 3.
[0135] Example 9
[0136] The difference between this embodiment and embodiment 6 is that the amount of modified low-temperature expandable graphite used in preparing ultra-high-strength concrete for large-span steel tube arch bridge is different, specifically 5 kg; the rest is the same as embodiment 6.
[0137] Example 10
[0138] The difference between this embodiment and embodiment 6 is that the amount of modified low-temperature expandable graphite used in preparing ultra-high-strength concrete for large-span steel tube arch bridges is different, specifically 25 kg; the rest is the same as embodiment 6.
[0139] Comparative Example
[0140] Comparative Example 1
[0141] The difference between this comparative example and Example 6 is that the modified low-temperature expandable graphite for preparing ultra-high-strength concrete for large-span steel tube arch bridge is prepared by modified low-temperature expandable graphite Preparation Example 7, and the rest is the same as Example 6.
[0142] Comparative Example 2
[0143] The difference between this comparative example and Example 6 is that the raw material for preparing the ultra-high strength concrete for the large-span steel tube arch bridge does not contain modified low-temperature expandable graphite; the rest is the same as Example 6.
[0144] Comparative Example 3
[0145] The difference between this comparative example and Example 6 is that the amount of modified low-temperature expandable graphite used in preparing ultra-high-strength concrete for large-span steel tube arch bridge is different, specifically 30 kg; the rest is the same as Example 6.
[0146] Comparative Example 4
[0147] The difference between this comparative example and Example 6 is that the low-temperature expandable graphite used to prepare the ultra-high-strength concrete for the large-span steel tube arch bridge is not modified; the rest is the same as Example 6.
[0148] Performance testing
[0149] 1. Compressive strength: Test according to the relevant provisions of GB / T50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete".
[0150] 2. Early crack resistance: Refer to GB / T50081-2016 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete" to make standard test blocks. The test blocks are cured at 5°C for 2 hours and then at -15°C for 24 hours. The number of cracks per unit area and the total crack area per unit area are measured.
[0151] 3. Relevant determination of whether the concrete is separated from the steel pipe wall after pouring: pour concrete into a steel pipe with a diameter of 1000mm and a height of 5m, and observe whether the concrete structure is separated from the inner wall of the steel pipe after 28 days. The specific grading standards are: Grade A: tight fit, no obvious separation; Grade B: there are fewer gaps in the range of 0-1mm; Grade C: there are more gaps in the range of 1-3mm; Grade D: there are more gaps in the range of 3-5mm.
[0152] Relevant tests were carried out on different implementation plans, and the specific results are shown in Table 1.
[0153] Table 1 Concrete properties of different implementation schemes and detachment of steel tube concrete
[0154]
[0155] From the data results in Table 1, it can be seen that the compressive strength of the concrete obtained in this application can be significantly improved, and from the crack resistance, it can be seen that its crack resistance has also been significantly improved. This application adds modified low-temperature expandable graphite to concrete, and based on the advantage of the low density of the modified low-temperature expandable graphite, the modified low-temperature expandable graphite tends to float in the concrete slurry, so that it has the advantage of repairing and filling cracks and pores at the interface between concrete and steel pipe. When the concrete obtained in this application is used to prepare steel tube concrete, it can significantly improve the situation where the concrete is separated from the steel pipe, but it cannot completely avoid the separation of the two.
[0156] The modified polystyrene microspheres of the present application have a low density of polystyrene layers and contain micro-nano reinforcing agents. The modified polystyrene microspheres are used to prepare modified low-temperature expandable graphite. This type of modified low-temperature expandable graphite can fill the pores and cracks inside the concrete due to the heat absorption and expansion characteristics of the modified polystyrene microspheres and the low-temperature expandable graphite, thereby reducing the number and area of cracks caused by early concrete cracking, and ensuring the strength of the concrete through the micro-nano reinforcing agents.
[0157] Comparison of Example 3 and Example 4 shows that when preparing modified polystyrene microspheres, the selection of micro-nano basalt powder and nano silicon dioxide as micro-nano enhancers are both feasible solutions. The data results of Example 3, Examples 5-6 and Comparative Example 1 show that when preparing modified polystyrene microspheres, the co-addition of micro-nano enhancers and calcium ion compensators can significantly improve the crack resistance and compressive strength of concrete: the micro-nano enhancers are used to directly reinforce concrete, while the calcium ion compensators are formed by reacting with unhydrated cement particles in concrete to form calcium aluminate crystals or monosulfur hydrated calcium sulfate, hydrated calcium sulfoaluminate, etc. to achieve filling and reinforcement of smaller cracks and pores. Under the joint action of the two, the crack resistance and compressive strength of concrete can be significantly improved.
[0158] From the data results of embodiment 6-8, it can be seen that when preparing modified low-temperature expandable graphite, the weight ratio of low-temperature expandable graphite and modified polystyrene microspheres is suggested to be in the range of 1:(1.2-2.6). If the consumption of low-temperature expandable graphite is low (embodiment 7), then modified polystyrene microspheres are difficult to stably load on low-temperature expandable graphite, which will cause the effect of the direct compressive strength of concrete enhanced by micro-nano reinforcing agent and the effect of indirect compressive strength of concrete enhanced by calcium ion compensator to be significantly reduced, thereby showing that the compressive strength of concrete as a whole is reduced. If the consumption of low-temperature expandable graphite is too high (embodiment 8), then there will be more pores in low-temperature expandable graphite that are not filled by modified polystyrene microspheres, and it is only filled with pores after endothermic expansion, but the strength at this place is still not improved, thus also showing that the compressive strength of concrete as a whole is reduced.
[0159] From the data results of Example 6, Example 9-10 and Comparative Example 2-3, it can be seen that the amount of modified low-temperature expandable graphite added is recommended to be in the range of 5-25 parts (Examples 9-10). If no modified low-temperature expandable graphite is added or the amount of modified low-temperature expandable graphite is too high (Comparative Example 2-3), the compressive strength and crack resistance of the concrete will be significantly reduced. In addition, the results of Comparative Example 4 also show that adding only unmodified low-temperature expandable graphite will make it difficult to have both the effect of expanding to fill the gap and chemically reacting to fill the gap, thereby significantly reducing the crack resistance of the concrete, and the detachment phenomenon of the interface between the concrete and the steel pipe is also more obvious.
[0160] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A long-span steel tube arch bridge with ultra-high strength concrete, characterized in that: The raw materials include the following parts by weight: 550-650 parts of cement, 50-120 parts of fly ash, 680-720 parts of machine-made sand, 750-1000 parts of crushed stone, 120-150 parts of water, 4-10 parts of water reducer, 3-4.5 parts of steel fiber, 10-15 parts of expansion agent, and 5-25 parts of modified low-temperature expandable graphite; The modified low-temperature expandable graphite comprises low-temperature expandable graphite and modified polystyrene microspheres loaded in the low-temperature expandable graphite, wherein the modified polystyrene microspheres comprise a polystyrene layer and an auxiliary agent coated in the polystyrene layer; the auxiliary agent comprises a micro-nano reinforcing agent; The modified low-temperature expandable graphite is obtained by dispersing low-temperature expandable graphite and modified polystyrene microspheres in a weight ratio of 1:(1.2-2.6) in a solvent, adding a silane coupling agent, and dispersing and mixing. Taking the modified polystyrene microspheres as a reference, the modified polystyrene microspheres include the following raw materials in parts by weight: 3-6 parts of micro-nano enhancer, 76-96 parts of polymerization monomer, 2.4-5.6 parts of initiator, 1.6-7 parts of dispersant, and 0.8-5 parts of surfactant.
2. The ultra-high strength concrete for long-span steel tube arch bridge according to claim 1 is characterized in that: The particle size of the modified polystyrene microspheres is 20-500 μm.
3. The ultra-high strength concrete for long-span steel tube arch bridge according to claim 1 is characterized in that: The modified polystyrene microspheres are prepared by a method comprising the following steps: S1, mixing the polymerization monomer and the initiator evenly to obtain an initial mixed solution; S2, after the dispersant, surfactant, micro-nano enhancer and initial mixed solution are uniformly mixed, the temperature is raised to 90-100° C. for reaction to obtain initial microspheres; S3, the initial microspheres are obtained after washing, drying and sieving.
4. The ultra-high strength concrete for long-span steel tube arch bridge according to claim 1 is characterized in that: The polymerizable monomers are styrene and divinylbenzene in a weight ratio of 1:(0.08-0.12).
5. The ultra-high strength concrete for long-span steel tube arch bridge according to claim 1 is characterized in that: The auxiliary agent also includes a calcium ion compensator; taking the modified polystyrene microspheres as a reference, the raw materials of the modified polystyrene microspheres also include 0.2-2 parts of the calcium ion compensator.
6. The ultra-high strength concrete for the long-span steel tube arch bridge according to claim 5 is characterized in that: The calcium ion compensator is selected from any one or more of calcium formate, calcium hydroxide, calcium nitrite, calcium dodecylbenzene sulfonate and calcium lactate.
7. The ultra-high strength concrete for long-span steel tube arch bridge according to claim 1, characterized in that: The micro-nano reinforcing agent is selected from one or both of micro-nano basalt powder and nano silicon dioxide.
8. The method for preparing ultra-high strength concrete for a long-span steel tube arch bridge according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: 1) Mix the machine-made sand and gravel in proportion and stir evenly, then add cement, fly ash and expansion agent and continue to stir evenly; 2) Mix water and water reducer and stir evenly, add 50-70wt% of the mixed water and water reducer to the mixture obtained in 1) and stir evenly, then add modified low-temperature expandable graphite and steel fiber, stir evenly, then add the remaining amount of mixed water and water reducer and stir evenly to obtain a mixed concrete mixture; 3) pouring the concrete mixture into a mold and curing it to obtain the ultra-high-strength concrete for the long-span steel tube arch bridge.
Citation Information
Patent Citations
Anti-crack concrete
CN108164218A
Large-volume concrete and preparation method thereof
CN108793887A
Ultrahigh-strength self-compaction micro-expansion steel pipe-encased concrete and preparation method thereof
CN109678433A
Winter application micro-expansive concrete and preparation method thereof
CN114716208A